Clasificación morfológica de células endoteliales de venas del cordón umbilical humano en imágenes digitales de cultivos in vitro. - Escobedo Nicot, Miriela Milagros; Herold García, C. Silena; Ferreira Gomes, C. Ligia; Delgado Font, Wilkie Ernesto; Machado, Camila; Monteiro Pereira, C. Elisângela (MEDISAN, 2018)
A descriptive and cross-sectional study was carried out from July to October, 2017, by specialists of the Oriente University and the University of Sao Paulo, Brazil, to analyze from the morphological point of view endothelial cells of the human umbilical cord veins, which were present in digital images of 2D in vitro cultures, treated with the βGPI. The cellular supervised classification was proposed considering 3 classes: circular, distorted elongated and distorted not very elongated, according to the coefficients of elliptic and circular shapes, all that allowed to identify outstanding cellular forms. To compare the results of the control and treated samples, the intervals of confidence were calculated for each of the classes, with a 95 % level of confidence. It was concluded that the analysis of the morphological disorders in vitro can be used in early 2D cultures (24 and 48 hours) for the quantification of the angiogénesis.